Selulosa Bakteri Terimpregnasi Nanopartikel Perak dari Sari Pelepah Kelapa Sawit dan Sifat Antimikrobanya - Wardatul Husna Irham; Syarifah Yusra; Hari Gunawan; Marzuti Isra; Sajaratud Dur (Jurnal Penelitian Pendidikan IPA, 2025)
Palm oil frond sap (NPS), rich in fermentable sugars and essential minerals, is a renewable substrate for the production of biocompatible biomaterials. This study aims to review the utilization of  of OPFJ as a culture medium for BC biosynthesis, its functionalization with silver nanoparticles (AgNPs), and the potential of the resulting composite’ for wound dressing applications. The method used was a literature review by collecting the latest and most recent journals, recording and analyzing the results of the utilization of OPFJ with AgNPs. The results showed   that OPFJ-based BC exhibits nanofibrillar morphology, high crystallinity, and good mechanical stability. The incorporation of AgNPs enhances antimicrobial activity against both Gram-positive and Gram-negative bacteria, providing a dual-functional dressing material. Nonetheless, limitations persist in silver release control, cytotoxicity management, and large-scale production. Future studies should focus on pretreatment optimization of OPFJ, green synthesis of AgNPs, and in vivo evaluations to ensure clinical viability.